Righting response and electrocardiographic evaluation of juvenile tambaqui (Colossoma macropomum) (Cuvier, 1818) exposed to immersion baths with different concentrations of bushy lippia essential oil (Lippia alba) - Thaysa de Sousa Reis; Clarissa Araújo da Paz; Daniella Bastos de Araújo; Luciana Eiró Quirino; Yris da Silva Deiga; Tays Mata Câmara; Moisés Hamoy (PLoS ONE, 2025)
In recent years, the use of natural products as alternatives to synthetic anesthetic agents has gained notoriety in aquaculture. Among the essential oils studied, Lippia alba has attracted attention due to its diverse pharmacological properties, including sedative and anesthetic effects. This study aims to evaluate the anesthetic activity of Lippia alba essential oil (LAEO) to propose a therapeutic window for its use in tambaqui (C. macropomum). In this research, juvenile tambaqui (10.9 ± 5.9g, n = 90) were submitted to anesthetic baths with LAEO at concentrations of 80–140 μL.L-1 for behavioral assessment and electrophysiological recordings. The findings showed that all concentrations were effective in inducing the loss of posture reflex and its subsequent reversible return. However, electrocardiographic recordings at concentrations of 120 and 140 μL.L-1 revealed alterations in the graph elements, indicating more intense bradycardia and atrioventricular block during anesthetic induction. Nevertheless, during the anesthetic recovery period, cardiac normality was restored at all tested concentrations, although more slowly at the highest concentration (140 μL.L-1). Thus, we conclude that this oil is safe for providing short-term anesthesia at concentrations between 80 and 100 μL.L-1 in C. macropomum specimens.